Gravity anomalies and magmatism along the western continental margin of the British Isles - Watts, A; Fairhead, J (1997)
Seismic data show that the western margin of the British Isles in the region of the Hatton Bank comprises a thin wedge of sediments, an extrusive volcanic sequence, stretched continental crust, and a thick high-velocity lower-crustal body. The sediments represent a load on the surface of the stretched crust, which should subside under their weight. The extrusive volcanic rocks defined by a seaward-dipping reflector sequence, were emplaced in the crust during the later stages of rifting. The lower-crustal body has been interpreted as underplated material which re-thickens the crust and causes uplift. Backstripping techniques have been used to evaluate the contribution of sediment loading and underplating to the observed crust and mantle structure and isolate the initial rift configuration of the margin. The contribution of these processes depends, however, on the elastic thickness, T e, of stretched lithosphere. We have constrained T e by computing the combined gravity anomaly of rifting, sedimentation and underplating and comparing it to the observed free-air gravity anomaly. Underplating gives rise to a distinct pattern of gravity anomaly 'highs' and flanking 'lows': the highs reflect the relatively dense uplifted crust and the lows less dense underplated material. The best fit between observed and calculated anomalies is for a model in which the T e of stretched lithosphere is low (<5 km) and the width of the initial rift is narrow (<75 km). Since T e is low, isostatic anomalies at the margin would be expected to be of small-amplitude and this is indeed the case at the Hatton Bank margin. Sensitivity studies show that large-amplitude isostatic anomalies would be expected, however, if T e is high - with negative anomalies of up to 30 mGal over the underplated region and positive anomalies of up to 10 mGal in flanking regions. Such anomaly patterns are seen west of Ireland and Scotland suggesting that underplating may be a widespread feature of the British Isles margin.